2017
DOI: 10.2147/jhl.s137071
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction among early and mid-career dentists in a metropolitan dental hospital in China

Abstract: A growing body of research has examined career satisfaction among dentists using a standardized instrument, dentist satisfaction survey (DSS). This project examined career satisfaction of early to mid-career dentists in China, a population whose career satisfaction, heretofore, has not been studied. This is an especially critical time to examine career satisfaction because of health care reform measures being implemented in China. A culturally sensitive Chinese-language version of the DSS (CDSS) was developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 22 publications
6
34
2
3
Order By: Relevance
“…The number of moderately satisfied, satisfied, and very satisfied physicians and dentists and sample sizes were pooled, resulting in an overall weighted percentage of 60% (95% CI 53%-67%), representing 14 113 physicians and dentists with substantial heterogeneity (I 2 = 98.21%; P < .001) ( Figure 4A). 46,47,52,53,55,58,59,81,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] Palmer-Morales et al, 40,41 2005 He et al, 87 Esquivel-Molina et al, 45 2007 Huri et al, 93 2016 Salem et al, 92 2018 Beltrán et al, 44 2004 Montenegro et al, 42 insufficient number of studies within each group. This concern was supported by a metaregression of dichotomous data, which suggested that job satisfaction levels did not differ significantly across countries with different income levels, but it was significantly higher among dermatologists (regression coefficient, 0.45; 95% CI, 0.13-0.89; P = .045) compared with other specialties (eAppendix 5 in the Supplement).…”
Section: Studies Were Published Between 1982 and 2018 Primarily Inmentioning
confidence: 99%
“…The number of moderately satisfied, satisfied, and very satisfied physicians and dentists and sample sizes were pooled, resulting in an overall weighted percentage of 60% (95% CI 53%-67%), representing 14 113 physicians and dentists with substantial heterogeneity (I 2 = 98.21%; P < .001) ( Figure 4A). 46,47,52,53,55,58,59,81,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] Palmer-Morales et al, 40,41 2005 He et al, 87 Esquivel-Molina et al, 45 2007 Huri et al, 93 2016 Salem et al, 92 2018 Beltrán et al, 44 2004 Montenegro et al, 42 insufficient number of studies within each group. This concern was supported by a metaregression of dichotomous data, which suggested that job satisfaction levels did not differ significantly across countries with different income levels, but it was significantly higher among dermatologists (regression coefficient, 0.45; 95% CI, 0.13-0.89; P = .045) compared with other specialties (eAppendix 5 in the Supplement).…”
Section: Studies Were Published Between 1982 and 2018 Primarily Inmentioning
confidence: 99%
“…Each tool has its own characteristics, target population, and usage focus, and they are not completely uniform. Tools for measuring work satisfaction in medical staff include universal scales (such as those used for all service staff [ 21 ], healthcare service staff [ 17 , 22 ], etc., and specific scales (such as those used for hospital doctors [ 23 , 24 ], hospital nurses [ 25 ], dentists [ 26 ], nursing home nurses [ 27 ], etc.). The measurement populations for these scales may be broad or have a finer professional classification [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results in the full model in Table 4 indicate that dentists in mid-large hospitals (with 101–200 employees) and the small hospitals (with less than 50 employees) have a much higher level of EI. The overall professional satisfaction of a dentist’s career in China is most associated with factors such as respect, delivery of care, income, and patient relations [ 67 ]. The large hospitals in China, those with top tertiary connections, are always regarded with strong respect and supported with various types of social and financial resources.…”
Section: Discussionmentioning
confidence: 99%